Proactive caching and personalized delivery mechanism of heterogeneous content for MAR applications in the Metaverse - XU Siya; FU Qimeng; GUO Shaoyong (Tongxin xuebao)
Addressing the issues of heterogeneous data content transmission and response latency in mobile augmented reality (MAR) applications, a proactive caching and personalized delivery mechanism of heterogeneous content for MAR applications in the metaverse was proposed. Firstly, considering user characteristics and edge node service capabilities, a user behavior and resource aware edge collaboration service domain (ECSD) construction method was proposed. Then, based on the ECSD, heterogeneous content pre-caching mechanisms based on storage space division and user preference prediction were designed. Specially, by introducing the personalized recommendation mechanism of foreground content, a differentiated delivery strategy of foreground content was designed. Simulation results show that the proposed mechanism outperforms NCPCR, CCS-AGP, and AIEC-RSC strategy in terms of cache hit rate, average response latency for foreground content and heterogeneous content.